Biological Excess Sludge Reduction in Municipal Wastewater Treatment by Chlorine - TAKDASTAN, AFSHIN; AKBAR AZIMI, ALI; JAAFARZADEH, NEMATOLLAH (Asian Journal of Chemistry, 2010)
As an alternative solution of sludge reduction, recently a chlorinationcombined aerobic biological process such as activated sludge has been developed for minimizing excess sludge production. In this study, Two sequencing batch reactor (SBR) reactors with of 20 L being controlled by on-line system are used. After providing the steady state in the reactors, along the 6 month research sampling and testing parameters such as chemical oxygen demand (COD), mixed liquid suspended solid (MLSS), mixed liquid volatile suspended solid (MLVSS), dissolved oxygen (DO), specific oxygen uptake rate (SOUR), sludge volume index (SVI), residual chlorine and yield (Y) coefficient were done. The results showed that during the solid retention time of 10 days the kinetic coefficient of Y (the biomass production efficiency) and Kd (endogenous efficiency) was 0.58(mgBiomass/mgCOD) and 0.58(1/day), respectively. At the next stage of research, different concentrations of chlorine in the reactor were used intermittent to reduce the excess biological sludge production. The results showed that the chlorine concentrated as 0.23 g per gram MLSS of 1 L of return sludge to the reactor is able to reduce the biomass coefficient from 0.58 to 0.33 (with approximate 45 % reduction of excess sludge) but the soluble COD slightly increased in the effluent. Besides the COD removal coefficient has decreasingly changed from 95 % in blank reactor to 80 %. In the 0.32 g chlorine/g MLSS of 1 L of return sludge to the reactor almost no excessive sludge was produced and the COD removal coefficient went down to less than 44 %. While the amount of SOUR and SVI in this consumed chlorine concentration reduced 3 mgO2/ h.gVSS and 17 mL/g, respectively.